Evaluation of Quality Improvement through Self Quality Audits: A Case in Lamp Industry - Umesh Bhatia; N. Sohani (New Approaches in Engineering Research Vol. 11, 2021)
Self-auditing is a useful method for continuous quality improvement. This method is being used to evaluate the quality ofCFL’s (Compact Fluorescent Lamps) manufactured in the company. Self-audits were undertaken on the shop floor and afterwards at the user’s end in this project. The results of both are reported in this study. For the improvements made cost increased was about 0.2% but benefits were substantial which increased the profitability of the company and gained the customer confidence.